2022
DOI: 10.3390/s22052053
|View full text |Cite
|
Sign up to set email alerts
|

High-Accuracy Event Classification of Distributed Optical Fiber Vibration Sensing Based on Time–Space Analysis

Abstract: Distributed optical fiber vibration sensing (DVS) can measure vibration information along with an optical fiber. Accurate classification of vibration events is a key issue in practical applications of DVS. In this paper, we propose a convolutional neural network (CNN) to analyze DVS data and achieve high-accuracy event recognition fully. We conducted experiments outdoors and collected more than 10,000 sets of vibration data. Through training, the CNN acquired the features of the raw DVS data and achieved the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…9, and then the valid IMF components are judged using Pearson correlation coefficient (PCC), and finally the signals are identified using one-dimensional convolution, and the identification accuracy of the intrusion signals collected in the experimental environment can reach 98.3%. In 2022, Ge 53 et al normalized the data in order to obtain the features of the original DVS only, and achieved an accurate classification of multiple vibration events by identifying the spatio-temporal data, and the accuracy could reach 99.9%. In the same year, Xu 54 et al proposed to suppress the random noise of the original data using moving average method, record the difference between two adjacent Rayleigh backward scattering record channels, and normalize the difference results, and convert the processed 2D data into images for network training and testing.…”
Section: Empirical Modal Decompositionmentioning
confidence: 99%
“…9, and then the valid IMF components are judged using Pearson correlation coefficient (PCC), and finally the signals are identified using one-dimensional convolution, and the identification accuracy of the intrusion signals collected in the experimental environment can reach 98.3%. In 2022, Ge 53 et al normalized the data in order to obtain the features of the original DVS only, and achieved an accurate classification of multiple vibration events by identifying the spatio-temporal data, and the accuracy could reach 99.9%. In the same year, Xu 54 et al proposed to suppress the random noise of the original data using moving average method, record the difference between two adjacent Rayleigh backward scattering record channels, and normalize the difference results, and convert the processed 2D data into images for network training and testing.…”
Section: Empirical Modal Decompositionmentioning
confidence: 99%
“…The working principle of Ф-OTDR technology is that when the external disturbance action is used for sensing the optical fiber, the refractive index of the sensing fiber will be changed [5,6], so that the Rayleigh scattered light will produce phase modulation, and the intensity or phase information of the backward Rayleigh scattered light pulse signal in the fiber can be distributed sensing. After the coherent pulsed light is injected into the sensing fiber through the circulator, the generated backward Rayleigh scattered light is returned to the front end of the fiber, and is received by the photodetector through the circulator, and the external strain change information is restored by demodulation by the demodulation unit [7].…”
Section: φ-Otdr Working Principlementioning
confidence: 99%
“…One notable approach in [ 11 ] introduced a self-supervised DL method aimed at improving DAS measurements via mitigating spatially incoherent noise with unknown characteristics. In [ 12 ], different pre-processing methods for the input to various DL models were compared, and an accuracy of 99.2% in a four-way classification task was achieved, highlighting the importance of the initial data representation fed into a DL model. In [ 13 ], classical ML methods and DL methods were compared, and it was concluded that the best approach depends on the data regime: In the low-data setting (usually at a project’s beginning), classical ML approaches dominate DL methods, as neural networks tend to overfit on spurious correlations.…”
Section: Introductionmentioning
confidence: 99%